Windows 2000 Disk IO Performance - Chung, Leonard; Gray, Jim; Horst, Robert; Worthington, Bruce (2000)
This paper is an empirical study of the random and sequential I/O performance of Windows 2000™ using the NT File System. It continues the work done by Riedel, et. al. in their 1997 paper exploring sequential IO performance under Windows NT 4.0™. This paper explores the performance and overhead of today’s Intel Pentium III™ based memory and IO subsystems, including the processor bus, the PCI bus, the disk controllers, the SCSI and IDE buses, and the disk media. It also examines the performance available from IDE RAID, a relatively new technology built from inexpensive IDE disks. Network IO performance is briefly covered. We describe how to achieve good throughput, and discuss the major bottlenecks. While Riedel’s model of software performance remains largely unchanged, increases in hardware performance have made the 32bit, 33MHz PCI bus the dominant bottleneck reaching saturation with three disks.